The influence of parental eating patterns on the nutritional status of Manado city children aged 6-24 months - Agustina, Rakhmawati; Puji Ati, Endang (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2022)
Parental eating habits have a positive effect on children's nutritional health. Numerous studies have examined children's eating patterns; however, few studies have examined the association between parental eating patterns based on the dimensions of demandingness and responsiveness in children and the nutritional status of 6- to 24-month-old children. This study aimed to examine the relationship between parental dietary habits and the nutritional status of children aged 6–24 months in Manado City. The research employed a quantitative approach with a cross-sectional design in the working area of the Ranomut Health Center, which included six neighborhoods from three villages: Paal 2, Ranomut, and Perkamil. This village was chosen because it has the highest concentration of children under the age of five in the Ranomut Health Center's service area. In this study, 96 samples were selected using the method of purposive sampling based on the criteria established by the researcher. The instrument used was the validated and reliable Feeding Practices and Structure Questionnaire for Infants, followed by data analysis using the Spearman rank test. The respondents' parental eating styles were authoritarian (31.3%), permissive (27.1%), democratic (20%), and negligent (20%). The nutritional status of children under the age of five was 26% malnourished and 74% well-nourished. The Spearman rank test resulted in a p-value of 0.674. This can be attributed to other factors, such as family composition and age-inappropriate food portions.